2007
DOI: 10.1242/jcs.03471
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase-induced activation of the gp130/Tyk2/Stat3 pathway mediates a pro-inflammatory effect in human mesangial cells via expression of the anaphylatoxin C5a receptor

Abstract: J. Zwirner, who produced the 20/70-antibody is his laboratory, is retracting his authorship from this paper. The reasons for the retraction are (1) he was not informed about the manuscript before it was published and (2) he could not observe, under the experimental conditions used in his laboratory, the immunoreactivity described in Fig. 10. All authors accept this decision, which is the result of an agreement mediated by the Ombudsman of the German Research Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Our observations are also in line with previous findings from our groups and those of others pointing to uPAR proinflammatory [40] and proatherogenic potential [41]. They also strengthen the previously demonstrated interference of uPAR with the complement cascade controlling C5aR expression and related functional effects [6,7]. We found that C5aR expression in atherosclerotic lesions was significantly impaired in uPAR -/ -/LDLR -/ -mice.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our observations are also in line with previous findings from our groups and those of others pointing to uPAR proinflammatory [40] and proatherogenic potential [41]. They also strengthen the previously demonstrated interference of uPAR with the complement cascade controlling C5aR expression and related functional effects [6,7]. We found that C5aR expression in atherosclerotic lesions was significantly impaired in uPAR -/ -/LDLR -/ -mice.…”
Section: Discussionsupporting
confidence: 93%
“…Color images available online at www.liebertpub.com/scd VSMC and in VSMC phenotypic modulations [8,23]. Our previous studies point to uPARs ability to interfere with the complement system and, in particular, to control C5aR expression and to affect by this way C5aR-directed functional effects [6,7]. To examine whether uPAR might control C5aR upregulation in MSC during osteogenic differentiation, uPAR was downregulated in MSC by means of a lentivirusbased interfering RNA (Supplementary Fig.…”
Section: Fig 1 Mesenchymal Stem Cells (Msc) Undergo Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…uPAR or uPA overexpression has been reported in many human cancers and shown to predict poorer prognosis in patients with breast, prostate, hepatocellular, and pancreatic cancers. [17][18][19][20] Interaction of uPAR and uPA has also been shown to lead to Stat3 phosphorylation and activation, a critical cell survival transcription activator, [21,22] and Stat3 activation has been associated with resistance to cisplatin-based chemotherapy in lung and ovarian cancers. [22,23] Recently, global gene expression and genetic/ epigenetic analysis of HNSCC tumors and cells have identified a large number of molecular alterations associated with cisplatin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] Interaction of uPAR and uPA has also been shown to lead to Stat3 phosphorylation and activation, a critical cell survival transcription activator, [21,22] and Stat3 activation has been associated with resistance to cisplatin-based chemotherapy in lung and ovarian cancers. [22,23] Recently, global gene expression and genetic/ epigenetic analysis of HNSCC tumors and cells have identified a large number of molecular alterations associated with cisplatin resistance. [24,25] In the current study, to investigate the phenomena of acquired cisplatin resistance in HNSCC, we performed gene expression profiling of cisplatin sensitive and resistant cells isogenic HNSCC cell lines.…”
Section: Introductionmentioning
confidence: 99%